2021
DOI: 10.4103/jfmpc.jfmpc_412_21
|View full text |Cite
|
Sign up to set email alerts
|

Association of Obstructive Sleep Apnea with Nocturnal Hypoxemia in Metabolic-Associated Fatty Liver Disease Patients

Abstract: Rationale: Obstructive sleep apnea (OSA) is often seen among obese individuals and the obesity has a linear association with MAFLD. The contribution of chronic intermittent nocturnal hypoxia of OSA and association of MAFLD with OSA is an unmet need. The present study aimed to determine the etiology, impact and association of OSA severity and nocturnal hypoxemia among patients ofChronic liver disease (CLD). Methods: In this study, analysis of the medical records and clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…Recently, a study involving a cohort of patients with chronic liver disease who underwent screening polysomnographies found that patients with MAFLD have a higher prevalence of OSA, a higher likelihood of severe OSA, and more severe nocturnal desaturation compared with non-MAFLD patients. 19 In agreement with findings by Tomar et al, 19 our study found that patients with MAFLD had higher levels of AHI and ODI, as well as worse nocturnal desaturation parameters. We further found that ODI was an independent risk factor for MAFLD.…”
Section: Discussionsupporting
confidence: 92%
“…Recently, a study involving a cohort of patients with chronic liver disease who underwent screening polysomnographies found that patients with MAFLD have a higher prevalence of OSA, a higher likelihood of severe OSA, and more severe nocturnal desaturation compared with non-MAFLD patients. 19 In agreement with findings by Tomar et al, 19 our study found that patients with MAFLD had higher levels of AHI and ODI, as well as worse nocturnal desaturation parameters. We further found that ODI was an independent risk factor for MAFLD.…”
Section: Discussionsupporting
confidence: 92%
“…Second, we used different cutoff points for a combination of PIVKA-II and AFP as discussed earlier. Third, some associated factors with hepatitis virus or fatty liver such as sleep apnea were not studied (33)(34)(35)(36)(37)(38). No predictor for HCC was studied as well as systematic review (39)(40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
“…Extra-hepatic complications Cardiovascular disease 22 MAFLD better identifies patients with worsening of atherosclerotic cardiovascular disease risk than NAFLD. Obstructive sleep apnea 46 MAFLD patients have higher prevalence and greater severity of obstructive sleep apnea and worse nocturnal desaturation parameters as compared to non-MAFLD patients. Chronic kidney disease 8 MAFLD identifies patients with chronic kidney disease better than NAFLD.…”
Section: Hepatic Complicationsmentioning
confidence: 96%
“…13 At present, some conclusions have been drawn on the clinical manifestations and extrahepatic complications of MAFLD (Table 1). 8,[21][22][23][44][45][46] Huang et al 47 confirmed that there is no difference in steatosis, hepatitis, and fibrosis between MAFLD and NAFLD. The MAFLD definition better identifies a group with fatty liver and significant fibrosis evaluated by non-invasive tests.…”
Section: Insulin Resistancementioning
confidence: 99%